Перестройка системы обучения и воспитания в школах и детских образовательных учреждениях в годы Великой отечественной войны - Александрова, Г.И.; Александров, Д.В.; Шкода, Н.А. (Культура народов Причерноморья, 2013)
В научной статье исследуется проблема реорганизации учебно-воспитательного процесса в школах, детдомах и интернатах советского государства, адаптация их работы к условиям военного времени. Авторы анализируют возникшие трудности предоставления образовательных услуг, а также систему мероприятий советского государства и общества по восстановлению нормальной работы детских образовательных учреждений. Раскрываются трудности всеобуча, нормативно-правовая база работы школ, интернатов, военных училищ. У науковій статті досліджується проблема реорганізації навчально-виховного процесу в школах, дитбудинках і інтернатах радянської держави, адаптація їх роботи до умов військового часу. Автори аналізують виниклі труднощі надання освітніх послуг, а також систему заходів радянської держави і суспільства по відновленню нормальної роботи дитячих освітніх установ. Розкриваються труднощі всеобучу, нормативно-правова база роботи шкіл, інтернатів, військових училищ. The article is devoted to the investigation of the questions of educational policy of Soviet state during the Great Patriotic war, namely to the analyses of social measures for reviving institutions of school education and child protection, conditions under which school children had opportunity to continue the process of study. In the article is probed the problem of reorganization of an educational process in schools, military and boarding-schools of the Soviet state, its adaptation to the terms of war-time. Authors analyze arising difficulties of educational services, and system of measures of the Soviet state and different subdivisions of folk education on proceeding normal work of child's educational establishments. Are discussed difficulties of mass education, normative-legal base of work of schools. The investigation of educational policy of soviet schools during the Great Patriotic war allows to extend horizons of meaningfulness of humanistic type of education. Being based on historical material authors of the article demonstrate complications of managing of educational tasks which appeared in war-time, the necessity of operative reforms, meaningfulness of legal measures and actual possibilities of proceeding in work of different subsections of school education. Authors suppose that the results of such historical research can be useful for the prophylaxis of negative tendencies in an educational sphere.